The Tutoring Industry in Hong Kong: From the Past Four Decades to the Future. (March 2019) - Eng, Richard
Purpose: This article sheds light on the historical changes in the tutoring industry and discusses the nature and driving forces of tutoring in the Hong Kong context. Based on the historical overview, this article introduces new developments in tutoring and discusses how tutoring fits into the bigger education picture. Design/Approach/Methods: Private tutoring in Hong Kong saw its takeoff in business in the 1980s, when the economy started to boom and parents were more willing to spend money on their children's education. These parents hoped that their children, by receiving university education, could improve their families' lives and secure a brighter future. Public examinations were used as a screening tool to select the cream of the crop for university admissions. Therefore, for many local mainstream school students, passing the public examinations with flying colors became the be-all and end-all of their studies. Tutorial schools regarded their fears as an opportunity and devised courses to suit their needs and allay their fears. Findings: More recently, educational reform, declining birth rate, and technological advances have brought challenges for tutoring businesses. They have explored new markets and changed the mode of operation to increase student intake and cut costs. It is expected that local tutorial schools, in particular the big tutorial-school chains, will provide more online courses for learners from early childhood to adult and will reduce the number and scale of off-line courses. Also, we may see a new kind of "star" tutors catering not to local mainstream school students but to their local international school counterparts. Originality/Value: Literature on tutoring in Hong Kong mainly investigates the phenomenon in recent times, specifically the past two decades. This article is the first attempt to draw a holistic picture of tutoring's historical development from an industrial perspective.